Penerapan Kaidah Bahasa Indonesia: Fonologi, Morfologi, dan Analisis Kesalahan - Andi Amanda Nur Istiqomah; Rahma Ashari Hamzah; Sitti Mufidah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The Indonesian language has linguistic rules that must be applied correctly, especially in the aspects of phonology and morphology. Errors in the use of Indonesian often occur due to a lack of understanding of these rules. This study aims to analyze the application of Indonesian language rules in phonology and morphology and identify common mistakes. The research method used is literature review, referring to various relevant academic sources. The analysis results indicate that phonological errors include vowel reduction, phoneme substitution, and sound assimilation, while morphological errors involve affixation, reduplication, and word composition. The main factors contributing to language errors include the influence of regional languages, lack of understanding of standard rules, and the habit of using informal language in daily communication. By understanding the types of errors and their causes, it is hoped that society can enhance its language skills to align better with linguistic standards.